Exclusive J/ψ production at the LHC in the kT factorisation approach. (24th January 2017) - Jones, S P; Martin, A D; Ryskin, M G; Teubner, T
Abstract: The recent LHCb data for exclusive J / ψ peripheral production at 13 TeV motivate an improved 'NLO' analysis to estimate the gluon distribution at low x in which we re-calculate the rapidity gap survival factors and use a more precise expression for the photon flux. We comment on the difference between the k T and collinear factorisation approaches.